Analysis of Misconception on Solubility and Solubility Product Constant (Ksp) Using Three-Tier Multiple Choice Test (Journal of Innovative Science Education, 2018)
The research aims to: analyze student's misconception on solubility and solubility product constant (Ksp) using the instrument of three-tier multiple choice test, and know the percentage of student's misconception. The research method used a mixed method with sequential explanatory strategy. Data collection technique was collected by diagnostic test using 20 questions of three-tier multiple choice that was completed by reasons and level of confidence, then the result of student's answer was analyzed. The result of the research shows that the diagnostic instrument test of three-tier multiple choice has fulfilled valid and reliable criteria. The implementation diagnostic instrument of three-tier multiple choice shows misconception percentage of solubility material was 5,272%, solubility product constant (Ksp) was 7,339%, the effect of same ions was 2,025%, the effect of pH on solubility was 4,597%, and sub-material of Ksp and the reaction process of sedimentation was 9,870%.